Using Artificial Intellect Systems to Attain Goals of Sustainable Development - N. V. Barinova; V. R. Barinov (Вестник Российского экономического университета имени Г. В. Плеханова)
At the current stage of social and economic relation development elaboration of artificial intellect technologies plays the key role and principle goals of sustainable development, where state policy of the Russian Federation is targeted, are connected with these systems. The article analyzed basic problems in the field of artificial intellect essential for reaching sustainable development goals. The authors provided examples of introducing artificial intellect tools to resolve problems of sustainable development presented by Russian and overseas researchers in recent years. The key content of the article is made by analyzing the current standing of artificial intellect in different aspects. The authors highlighted industries, where systems of artificial intellect work effectively, such as finance and economic sphere, public health, aero-space production, agro-industrial field and use of natural resources. The article shows operating artificial intellect systems and their impact on economy and sustainable growth. Arguments in favor of these systems are given, as well as their connection with ESG conception. Finally, conclusions about trends in artificial intellect development in times of digitalization were made.